Shifting the Education Paradigm: Why International Borrowing is No Longer Sufficient for Improving Education in China - Yong Zhao (ECNU Review of Education, 2018)
Purpose —The purpose of this article is to examine the consequences of mutual borrowing of educational policies and practices between the East and the West and implications for Chinese education. Design/Approach/Methods —This paper draws upon a wide variety of historical, cultural, and international assessment data. Findings —The analyses found that the mutual borrowing is unlikely to improve education to the extent that the future world demands. Originality/Value —Thus, the article concludes that instead of wasting resources and time on learning from each other's past, education systems around the world should work on inventing a new paradigm of education. China is in a unique position to work on the new paradigm.